Improving the Quality of Small, Medium and Micro Enterprises Production of Simple Financial Reports in Tahu Bandung Idola and Irma Crackers in West Cilebut Village - Muhammad Faza Aditya; Maria Magdalena Melani; Titiek Tjahja Andar; M. Nur Afifi; Siti Herlinda Triana Pebrianti; Aulia Putri; Siti Nurisma Ristiawan; Siti Saadah; Fitri; Tria; Maysanda; Ahmad Fachri Putra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community empowerment is an effort to prepare the community along with steps to strengthen community institutions so that they are able to realize progress, independence and prosperity in an atmosphere of sustainable social justice. Activities are carried out through the Real Work Lecture (KKN) program which is a community service-based activity to increase student empathy towards the conditions of the community and surrounding MSMEs. KKNTematic 2023 was held in West Cilebut Village, Sukaraja District, with service methods such as counseling and providing innovation. Results shows a positive response from MSMEs regarding high active community participation, including carrying out simple bookkeeping neatly, innovating brand designs, and legalizing NIB.